Addressing Equity: Assessing Inclusion and Diversity in Government Services, Operations, and Management - Tarmizi, Abdul Hafiz (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Equity is the use of justice to recognize each other’s rights, using equality for the same. On the other hand, equity adjusts the rules to certain conditions to make it fairer and more equitable in an organization. It also serves as a platform of justice and because it does not prescribe written laws, it only creates more democracy and also has a role in law. Enlightening managers and leaders on how to inculcate and seek a diverse workforce to increase productivity by employing all employees to their maximum potential, resulting in increased profitability and effectiveness. Because of the importance of business, organisational management, and human capital management, the topic has become one of the most thought-provoking problems now debated. To be competitive, one must learn to deal with a wide range of situations. This paper discloses that workplace diversity and inclusion boost employees' ability in critical thinking, solving problem, and their professional skills. These positive outcomes will eventually enable organizations to attract talent, improve corporate attractiveness, and improve performance, productivity, and finances. As a result, this paper highlights the historical background of the different races in their job scope before and after Merdeka, the results of the survey and interview session in regards to the inclusion of multiracial in their workplace, factors that less inclusion of other races in the workplace and the Islamic perspective of the inclusion diversity in any kind of area.